(untitled) (Global Journal of Human-Social Science, 2021)
Most religious tenets condemned corruption It looks at it as a crime against humanity and divinity The majority of Nigerians are religious adherent and their religions condemn corruption Despite this fact it is spreading geometrically in Nigerian society This paper examines religion and the extent of corruption in Nigeria It conceptualizes religion and corruption examine the roots of corruption in Nigeria The work used historical and descriptive methods in its analysis The study discovered poor wages high cost of living greediness bad leadership and pressure from extended families societal influence and attitude of recognizing only wealthy people moral decadence poverty and unemployment as roots of corruption in Nigeria The paper is of the view that for corruption to decrease in Nigerian society religious leaders and adherents should apply the religious tenets to their whole life They should not limit it to religious pretense only